Discriminant Validity of the Stress-Energy Questionnaire Regarding Work and Leisure Time - Emina Hadžibajramovic; Elisabeth Svensson; Gunnar Ahlborg (Örebro University School of Business, 2013)
Purpose: The Stress-Energy Questionnaire (SEQ) is an instrument developed to measure two aspects of mood at work. This study evaluates the discriminant validity of the SEQ when assessments are separated into work and leisure time. Furthermore, the use of the scale categories was explored with respect to gender. Methods: The data (n=2817, 84% women) came from a survey involving public health care employees and insurance office workers in western Sweden. As the data consist of ordered categories, a nonparametric statistical method for paired ordered categorical data was used. Results: A significant systematic disagreement meaning higher stress and energy levels at work compared to leisure time was found for all items in both women and men. According to our study, one can expect a higher level of stress and energy at work as compared to leisure time, but the high individual variations indicated heterogeneous data. Differences were also found between how men and women used the scale categories; for example, the endpoint categories not at all and very much were more often used by women, while men use the central categories hardly, somewhat, and fairly more frequently than women. Conclusion: This study showed that the two sets of items referring to work and leisure time, respectively, discriminate the responses. Distinction between work and leisure time is recommended when using this modified version of the SEQ. To use only work assessment would mean a loss of information.
Keywords: A10; 330; self-report instrument; discriminant validity; ordinal data